Advice to the FDA to Improve Its Proposed Guidelines to Rationalize Clinical Trials by Restricting Placebo Control, Preventing Low-Powered Studies, and Disallowing Studies Where Bioavailability Is Not Proven - Sarfaraz K. Niazi (Pharmaceuticals)
Randomized controlled trials (RCTs) are the gold standard for testing the safety and efficacy of new drugs and biologicals. The US Food and Drug Administration (FDA) has proactively improved the trial designs to make them scientifically rational while avoiding unnecessary human exposure. Several new guidelines by the FDA have come in 2024 that address consolidating the RCTs with the Real-World Evidence (RWE) trials, decentralizing the testing platforms, and allowing the point-of-use clinicians to participate. However, the issue of placebo control remains, which is part of RCTs, and it should be reduced or removed given the organic impact of placebo that compounds the efficacy evaluation (explanatory trials), as opposed to effectiveness trials (pragmatic trials), which measure the degree of beneficial effects in “real-world” clinical settings. Additionally, clinical trials with low study power should be allowed, and when the proof of bioavailability at the site of action is not present, it should be removed. It is advised that the FDA issue a comprehensive guideline to consolidate its several guidelines and consider the role of placebo in making drug development a more affordable exercise while meeting the requirement to minimize the abuse of humans in such trials.